Agricultural Exports, Tariffs and Growth - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2014)
This article presents a Ricardian model of trade with learning-by-doing to study the effect of barriers to trade in products with low growth potential on the long-run economic growth. The model shows that, when elasticity of demand for the product with a lower learning potential is lower than unitary, a reduction in the tariff imposed on this product, may shift the demand toward the product with a higher learning potential, thus enhancing economic growth in the exporter economy. Therefore, the current trend of reduction in tariffs on agricultural exports not only generates a positive welfare effect in the short run, but may similarly be beneficial for developing economies in the long run, since it also increases their incentive to develop sectors with higher growth potential.
Keywords: F11; F15; F41; O41; Q17; 330; trade barriers; agricultural export; learning-by-doing